Euphrasia Eye Drops in Preterm Neonates With Ocular Discharge: A Randomized Double-Blind Placebo-Controlled Trial - Meier-Girard, Delphine; Gerstenberg, Gisa; Stoffel, Liliane; Kohler, Therese; Klein, Sabine D.; Eschenmoser, Marco; Mitter, Vera Ruth; Nelle, Mathias; Wolf, Ursula (Frontiers in Pediatrics, 2020)
Aim: To investigate whether the early administration of Euphrasia eye drops® in preterm neonates presenting with ocular discharge fosters the resolution of the ocular discharge and reduces the need for topical antibiotic therapy, as compared to placebo. Methods: We conducted a randomized double-blind placebo-controlled trial at the University Children’s Hospital Bern, Switzerland. Preterm neonates with white, yellow, or green ocular discharge were included. Infants were randomly assigned (1:1) to the Euphrasia arm (Euphrasia eye drops®, Weleda AG, Arlesheim) or the placebo arm (NaCl 0.9%). Euphrasia or placebo was administrated at a dose of one drop in each eye four times a day over a period of 96 hours. The primary outcome was the treatment success, defined as no ocular discharge at 96 hours and no use of topical antibiotic therapy during the 96-hour intervention. Results: A total of 114 neonates were screened and 84 were randomized. Among neonates in the Euphrasia arm, 22 (55.0%) achieved our primary outcome compared to 21 (51.2%) in the placebo arm (p=0.85). In the Euphrasia arm, time to resolution of reddening tended to fall within the shorter bracket of 24 to 48 hours (24 (92.3%) versus 12 (80.0%) in the placebo arm, p=0.34) and relapse or first signs of reddening during the 96-hour intervention tended to be lower (3 (7.9%) eyes versus 8 (18.2%) eyes in the placebo arm, p=0.17). Tearing at 96 hours tended to be lower in the Euphrasia arm (5 (12.8%) eyes in the Euphrasia arm versus 12 (27.3%) eyes in the placebo arm, p=0.10). Discussion: Euphrasia did not significantly improve treatment success, defined as no ocular discharge at 96 hours and no use of topical antibiotic therapy during the 96-hour intervention. However, results suggest that Euphrasia may be of benefit for symptoms such as reddening and tearing, and thus improve the comfort of patients.